1989
DOI: 10.1007/bf02556019
|View full text |Cite
|
Sign up to set email alerts
|

Dual photon absorptiometry of the proximal tibia

Abstract: Bone mineral content (BMC) and bone mineral density (BMD) of the proximal tibia were determined by dual photon absorptiometry on 44 women, aged 23-87 years. The area of the tibia measured was a 2.01 cm region immediately distal to the medial and lateral tuberosities. Values of BMC ranged between 5.09 and 14.57 g and BMD between 0.380 and 1.180 g/cm2. Both tibial BMC and BMD declined with age and tibial BMD was significantly correlated with lumbar spine (r = 0.70), femoral neck (r = 0.73), and femoral trochante… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1991
1991
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…The age-related decay in BMC of the proximal tibia shows similar age-related trends as in other skeletal sites (Mazess 1982), and both Bohr and Schaadt (1987) and Checovich et al (1989) found similar age related decreases in bone mineral in the proximal tibia. Postmenopausal osteoporosis was clearly visible in the proximal tibia.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The age-related decay in BMC of the proximal tibia shows similar age-related trends as in other skeletal sites (Mazess 1982), and both Bohr and Schaadt (1987) and Checovich et al (1989) found similar age related decreases in bone mineral in the proximal tibia. Postmenopausal osteoporosis was clearly visible in the proximal tibia.…”
Section: Discussionsupporting
confidence: 75%
“…There is good evidence that previous fragility fractures are associated with an increased risk of subsequent hip fracture (Owen et al 1982;Lauritzen and Lund 1993), but also individuals who has sustained tibial fractures has an increased risk for later fragility fracture (Karlsson et al 1993a), and in an epidemiologic study by it was found that new lower extremity fractures of the tibia or femur in patients with a history of previous tibial shaft fractures were mainly ipsilateral. The loss of bone mineral of the hip and tibia associated with tibial shaft fractures may be considered of clinical importance with respect to the expected age related annual decay of bone mineral at these measuring sites (Schaadt and Bohr 1988;Aloia et al 1990;Bohr and Schaadt 1987;Checovich et al 1989;Petersen et al 1993). The early bone loss seems to be at least partially permanent (Karlsson et al 1993b;Kannus et al 1994b), and the potential for recovery have been considered to be even smaller following long-term immobilization (Jaworski and Uhthoff 1986;Minaire 1989).…”
Section: Discussionmentioning
confidence: 99%
“…With respect to the expected age related decay of bone mineral in the areas of interest measured in the present study (Bohr & Schaadt, 1987; Schaadt & Bohr, 1988; Checovich, Kiratli, Smith, 1989; Aloia, Vaswani, Ross, Cohn, 1990; Petersen et al, 1993), patients who had previously sustained an Achilles tendon rupture must be considered to be some years ahead in their natural osteoporotic process in the bones of the affected legs. Even though the initial decrease in bone mineral was below what has been observed after fractures of the lower extremities (Petersen et al, 1992; Petersen et al, 1997), the loss of bone mineral of 6.4%, 2.2%, and 6.8% for measurements in, respectively, the proximal tibia, femoral neck and greater trochanter one year after an Achilles tendon rupture must be considered to be of clinical importance with an increased fracture risk (Marshall, Johnell, Wedel, 1996).…”
Section: Perspectivesmentioning
confidence: 90%
“…11,25,26 Knees with the highest BMC would probably be in young individuals with a high level of physical activity and, most frequently, men; these are also parameters which are recognised as risk factors for early aseptic loosening. In a study from the Swedish Knee Arthroplasty Register which evaluated 41 233 knee arthroplasties undertaken between 1988 and 1997, it was found that the older the patient, the lower the revision rate for aseptic loosening.…”
Section: Discussionmentioning
confidence: 99%